2016
DOI: 10.1177/1938640016656780
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Toe Walking

Abstract: Prognostic, Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
1
13
0
2
Order By: Relevance
“…In a current review about toe walking, BW use was not included among the causes (19) . However the current literature does not show consistent data about the frequency and causes of idiopathic toe walking (17) . Pomarino et al (17) presented the genetic tendency of toe walking especially among boys and concluded that there may be other nongenetic factors.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In a current review about toe walking, BW use was not included among the causes (19) . However the current literature does not show consistent data about the frequency and causes of idiopathic toe walking (17) . Pomarino et al (17) presented the genetic tendency of toe walking especially among boys and concluded that there may be other nongenetic factors.…”
Section: Discussionmentioning
confidence: 78%
“…However the current literature does not show consistent data about the frequency and causes of idiopathic toe walking (17) . Pomarino et al (17) presented the genetic tendency of toe walking especially among boys and concluded that there may be other nongenetic factors. In our study gait disorders were higher among children who used BWs than non-users.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…[3][4][5] The cause of ITW is unknown. There are studies that attribute this to a family predisposition reporting an incidence of 34% to 42%, 5,6 while others claim that ITW has a relationship with a sensory processing disorder. 3,4 However, this has not been proven.…”
Section: Levels Of Evidence: Therapeutic Level Ii: Systematic Reviewmentioning
confidence: 99%
“…ITW is present in either gender; nevertheless, males with family predisposition are more likely to be affected. 6 The effectiveness of the treatment methods varies widely. There are conservative options and surgical approaches.…”
Section: Levels Of Evidence: Therapeutic Level Ii: Systematic Reviewmentioning
confidence: 99%